The significance of serum hepcidin on iron status in overweight and obese patients with iron-deficiency anemia - Abeer Anwer Ahmed (Iraqi Journal of Hematology, 2020)
BACKGROUND: Deficiency of iron is one of the most prevalent nutritional disorders, and obesity is an increasing nutritional problem, but only a few studies mention a possible association between them in Iraq. Adipocytes secrete adipokines, some of them are related to the inflammatory response in addition to hepcidin, a hormone that mediates iron metabolism. OBJECTIVES: This study aimed to assess the significance of serum hepcidin in obese patients with iron deficiency. PATIENTS MATERIALS AND METHODS: Ninty patients were separated into Group 1 (normal weight), Group 2 (30 overweight), and the Group 3 (30 obese). All patients were investigated by complete blood count, serum hepcidin, iron, total iron-binding capacity, and ferritin using the standard laboratory techniques. RESULTS: There were no significant differences among the groups regarding the severity of anemia, red cell indices, white blood cells, and platelets count. The obese group had significantly higher serum hepcidin and ferritin (P = 0.003, 0.040, respectively), while serum iron is lower. Serum hepcidin positively correlated with the serum ferritin but inversely correlated with serum iron. Increased hepcidin level in obesity could be related to inflammatory adipokines that effect on hepatic hepcidin transcription and hepcidin mRNA expression, in addition to the nonhepatic production of hepcidin in an autocrine manner; hepcidin, in turn, is responsible for low serum iron, but a high ferritin level in correlation to high hepcidin may explain by low-grade chronic inflammation associated with obesity. CONCLUSIONS: The severity of iron-deficiency anemia is not affected by body weight; however, significantly higher serum hepcidin and ferritin in the obese patient with a lower serum iron should be considered during the assessment of iron status in those patients.